2019
DOI: 10.1007/978-3-030-29374-1_41
|View full text |Cite
|
Sign up to set email alerts
|

Digital Inequalities: A Review of Contributing Factors and Measures for Crossing the Divide

Abstract: This literature review focuses on the digital divide in contemporary technologically and economically advanced societies. Prior research shows that the digital divide entails more than physical accessibility and points to issues of technology acceptance and actual use. Recurring digital divide factors outside socioeconomic characteristics were identified in the articles reviewed. These factors relate to personality traits, motivation and digital skills. The factors can be used as the basis for a personality mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Strengthening digital inclusion and overcoming digital divides is a difficult societal challenge. We can attempt to respond to it through various political measures, training and design tailoring (Hustad et al, 2019). The possibility of receiving social support and formal help with the use of ICTs is central to the prevention of digital inequality at the individuallevel (e.g.…”
Section: Reflection On the Resultsmentioning
confidence: 99%
“…Strengthening digital inclusion and overcoming digital divides is a difficult societal challenge. We can attempt to respond to it through various political measures, training and design tailoring (Hustad et al, 2019). The possibility of receiving social support and formal help with the use of ICTs is central to the prevention of digital inequality at the individuallevel (e.g.…”
Section: Reflection On the Resultsmentioning
confidence: 99%
“…As noted earlier, a comprehensive literature review by Hustad, Hansen, Skaiaa, & Vassilakopoulou, (2019) indicated that an individual's personality traits may influence engagement and utilisation of digital technology.…”
Section: Strategies For Reducing the Digital Dividementioning
confidence: 88%
“…The authors found digital illiteracy to be a great hindrance to effective engagement with digital technology and encourages IT professionals and public libraries to themselves be better educated in the nuanced nature of digital exclusion and socioeconomic status. Hustad, Hansen, Skaiaa, & Vassilakopoulou, (2019) undertook a literature review examining the digital divide in advanced nations with comparable technological and economic status. The authors found that there is more to closing the digital gap than just providing access.…”
Section: Not the Access But The Engagementmentioning
confidence: 99%
“…These reviews have been extended to understand how events such as Covid 19 promote or impede digital inclusion initiatives and propose possible solutions to overcome the digital divide for various demographic groups and in diverse geographic locations (Aissaoui, 2021;Esteban-Navarro et al, 2020). In addition, the reviews provide valuable perspectives on definitions and terminology, factors underpinning digital inclusion, the different groups affected, and they explore potential interventions to address challenges identified (Borg et al, 2019;Fang et al, 2019;Hustad et al, 2019).…”
Section: Recent Literature Reviews On Digital Inclusionmentioning
confidence: 99%